2014
DOI: 10.1590/s1517-83822014000200014
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers to evaluate the effects of temperature and methanol on recombinant Pichia pastoris

Abstract: Pichia pastoris is methylotrophic yeast used as an efficient expression system for heterologous protein production. In order to evaluate the effects of temperature (10 and 30 °C) and methanol (1 and 3% (v/v)) on genetically-modified Pichia pastoris, different biomarkers were evaluated: Heat stress (HSF-1 and Hsp70), oxidative stress (OGG1 and TBARS) and antioxidant (GLR). Three yeast cultures were performed: 3X = 3% methanol-10 °C, 4X = 3% methanol-30 °C, and 5X = 1% methanol-10°C. The expression level of HIF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
(44 reference statements)
0
10
0
2
Order By: Relevance
“…This observation agrees with the results obtained in recombinant P. pastoris at 10 °C. 8 The decrease in the formation of lipid peroxides is induced due to a drop in temperature. This may be because the temperature induces a modulation in the formation of membrane lipids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation agrees with the results obtained in recombinant P. pastoris at 10 °C. 8 The decrease in the formation of lipid peroxides is induced due to a drop in temperature. This may be because the temperature induces a modulation in the formation of membrane lipids.…”
Section: Discussionmentioning
confidence: 99%
“…For the reactivation step, 1 mL of frozen material was inoculated in 500 mL Erlenmeyer flasks containing 100 mL of the growth medium BMGY (buffered glycerol complex medium) (1% (w/v) yeast extract, 2% (w/v) casein peptone, 0.34% (w/v) yeast nitrogen base, 1% (w/v) ammonium sulfate, 100 mM buffer potassium phosphate pH 6.0, 4 × 10 −5 % (w/v) biotin, 1% (v/v) glycerol, 2% (w/v) casamino acids with deionized water) and incubated at 30 °C and 250 rpm for 19 h in a shaking incubator (Model SI-300, Jeio Tech, Seoul, Korea). 8 The reactivation step should be realized once because freeze–thaw stress affects the viability and activity of yeast cells, beside it has been reported that several cellular factors affect freeze–thaw stress tolerance. 36 , 37 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the use of glycerol as a cosubstrate could be an interesting, alternative strategy,13, 16 provided that it does not repress AOX1 promoter at relatively low level 14 . Based on this information, a typical rAb production by P. pastoris consists of three distinct phases: (a) glycerol batch phase to stimulate growth, (b) glycerol fed-batch phase for AOX1 derepression, and (c) methanol induction phase to express the recombinant protein 17, 18, 19. In the last phase methanol is typically pulsed repeatedly after complete depletion of substrate 20 …”
Section: Introductionmentioning
confidence: 99%
“…Verificou-se que em temperaturas acima de 32 °C ou muito baixas decai a expressão de proteínas heterólogas (COS et al, 2006;ZEPEDA et al,2014).…”
Section: Expressão De Proteínasunclassified